Just the facts, ma'am: Postsecondary education and labor market outcomes in the US - Harry J. Holzer; Erin Dunlop (Institute for the Study of Labor (IZA), 2013)
In this paper, we provide a comprehensive and up-to-date snapshot of the most important postsecondary education and labor market outcomes in the U.S. using two nationally representative sources of data: The Survey of Income and Program Participation (SIPP) and The National Educational Longitudinal Survey (NELS). We find that postsecondary educational attainment has risen modestly among young Americans over the past two decades, with greater gains in BA attainment in the 1990s and in certificate and AA attainment since 2000 (though attainment rose during the Great Recession at all levels). Both younger and older cohorts of blacks and Hispanics have made relative progress in the attainment of certificates and AAs but still lag behind whites in the entry into and completion of BA programs; completion rates in BA programs also lag substantially for those from low-income families or with weak academic achievement in high school. Young women (especially among whites and blacks) now achieve sub-BA and BA degrees at higher levels than their male counterparts and generally have higher achievement. There are labor market returns for all postsecondary credentials, including certificates and AA degrees, though these vary across field of study. Large gender gaps exist in field of study, with men more concentrated in high-paying fields. Lastly, we find that high school achievement measures can account for much of the racial gaps in BA completion and earnings and some of the gaps by family background, though they account for little of the continuing gender gap favoring young men in earnings.
Keywords: I23; I24; J24; 330; postsecondary education; earnings; labor market